(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In this article, the role of information technologies in medicine medical informatics at a medical university as a discipline considers issues not only of health informatization. First of all, medical information systems are tools designed for the daily work of a doctor and medical personnel,quality control of medical care, analysis of current medical and preventive work, monitoring of health indicators, management decision–making and economic forecast of the functioning of the health system.